2008
DOI: 10.1101/gr.081497.108
|View full text |Cite
|
Sign up to set email alerts
|

A resource for the simultaneous high-resolution mapping of multiple quantitative trait loci in rats: The NIH heterogeneous stock

Abstract: The laboratory rat (Rattus norvegicus) is a key tool for the study of medicine and pharmacology for human health. A large database of phenotypes for integrated fields such as cardiovascular, neuroscience, and exercise physiology exists in the literature. However, the molecular characterization of the genetic loci that give rise to variation in these traits has proven to be difficult. Here we show how one obstacle to progress, the fine-mapping of quantitative trait loci (QTL), can be overcome by using an outbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 41 publications
5
80
0
Order By: Relevance
“…), and this imposes a cluster structure in the data that, if not accounted for analytically, results in spurious associations in addition to genuine QTLs (13,40). A previous study using the HS rat population accounted for family structure by employing a significance threshold that takes into account these family relationships (18). In the current study, we have developed this approach further by not only taking family into account when determining the significance threshold, but also by including family as a random intercept in the regression model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…), and this imposes a cluster structure in the data that, if not accounted for analytically, results in spurious associations in addition to genuine QTLs (13,40). A previous study using the HS rat population accounted for family structure by employing a significance threshold that takes into account these family relationships (18). In the current study, we have developed this approach further by not only taking family into account when determining the significance threshold, but also by including family as a random intercept in the regression model.…”
Section: Discussionmentioning
confidence: 99%
“…When only a region of the genome is genotyped, however, multiple QTL modeling is not applicable. In their fine-mapping of a fear-related locus on a single chromosome, Johannesson et al (18) overcame this excess of potential false positives by adopting a stricter significance threshold in which family structure is incorporated into the threshold procedure. Here we developed this approach further by including sibship as a random intercept both in the HAPPY regression model (see Ref.…”
Section: Statistical Genetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…With this aim, the NIH-HS rat stock was formed through an eight-way cross among eight inbred rat strains (see "Methods" below; Hansen and Spuhler [22]). Recent genetic studies have demonstrated that the NIH-HS rat stock is a unique animal model for the simultaneous identification and fine mapping of QTLs (Quantitative Trait Loci) even to a gene resolution level (for reviews see [23,24]). From the phenotypic stand point, our behavioural and hormonal studies of the heterogeneous rat stock clearly indicate that the NIH-HS rat colony (established in our laboratory, at Autonomous University of Barcelona, in 2004) exhibits a behavioural "defensive" profile indicating that these animals are rather fearful and anxious, presenting a predominantly passive/reactive coping style as well as stressprone (i.e.…”
Section: Introductionmentioning
confidence: 99%